Effective Combination of Nigella sativa and Trigonella foenum-graecum Seed Extract on Wound Healing in Diabetic Mice - Susilowati, Retno; Rohmanningrum, Ulfa Maynisa (Jurnal Biodjati, 2023)
High levels of free radicals in diabetic wounds often cause chronic inflammation. Nigella sativa and Trigonella foenum-graecum seed extracts are rich in antioxidants and have anti-inflammatory effects. Trigonella foenum-graecum seed extracts can also accelerate the reepithelialization process in wound healing. This study aimed to determine the combination of ethanol extract of Nigella sativa and Trigonella foenum-graecum seeds on wound length and the number of neutrophils, macrophages, fibroblasts, and collagen density in the incision wound of diabetic mice induced by streptozotocin. T. This study used three types of controls, namely Normal (Normal mice,Â  HPMC 3%),Â  DM (Diabetic mice, HPMC 3%), and Iodine (Diabetic mice, Povidone Iodine 10%). Topical treatment with 70% ethanol extract ointment combined with Nigella sativa and Trigonella foenum-graecum in various variations, namely N (20%:0%), T (0%:10%), NT (10%:5%), Observations of the wound healing process were carried out on 3rd, 7th and 14th day. Data were analyzed using the One Way ANOVA and Duncan Multiple Range Test. The study's results by observing the morphology of the wound length on day 7th day showed that the combination treatment of extracts of Nigella sativa and Trigonella foenum-graecum resulted in the shortest wound, which was significantly different from the wound in untreated diabetic mice. In addition, diabetic wounds without treatment showed infection, and on the contrary, the infection did not occur in wounds treated with a combination of extracts of Nigella sativa and Trigonella foenum-graecum. The results of wound histology observations showed that the combination treatment of extracts of Nigella sativa and Trigonella foenum-graecum showed a decrease in inflammation which was indicated by a significant decrease in the number of neutrophil cells, macrophages, and accelerated reepithelialization of wound healing as indicated by a significant increase in the number of fibroblasts and collagen density since the third day of treatment.